2018
DOI: 10.1002/jcla.22696
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroidectomy decreases serum intact parathyroid hormone and calcium levels and prolongs overall survival in elderly hemodialysis patients with severe secondary hyperparathyroidism

Abstract: Background The objective of this study was to assess the effect of parathyroidectomy (PTX) treatment on prolonging overall survival (OS) as well as decreasing levels of intact parathyroid hormone (iPTH), calcium (Ca), and phosphorus (P) in elderly hemodialysis patients with severe secondary hyperparathyroidism (SHPT). Methods A total of 304 elderly hemodialysis patients with severe SHPT were consecutively enrolled in this cohort study. According to whether PTX operations were applied, patients were classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
(30 reference statements)
3
6
0
Order By: Relevance
“…However, the control of PTX on the rate of reaching the target range of laboratory indicators in patients with secondary hyperparathyroidism still needs to be further explored. Similar to a previous study [25], we found that the levels of iPTH, serum calcium, and phosphorus decreased significantly after PTX. In a recent large prospective, multicenter epidemiological observational study in France [26], 9010 incident patients were included.…”
Section: Discussionsupporting
confidence: 91%
“…However, the control of PTX on the rate of reaching the target range of laboratory indicators in patients with secondary hyperparathyroidism still needs to be further explored. Similar to a previous study [25], we found that the levels of iPTH, serum calcium, and phosphorus decreased significantly after PTX. In a recent large prospective, multicenter epidemiological observational study in France [26], 9010 incident patients were included.…”
Section: Discussionsupporting
confidence: 91%
“…The advantage of this operation is that the function of the transplanted glands can be monitored by measuring the iPTH levels of the bilateral forearms 23 . Our study showed that PTX was effective in the treatment of SHPT, which was consistent with the results of previous studies 4,24,25 . Patients who cannot tolerate surgery can be treated with ultrasound-guided thermal ablation.…”
Section: Discussionsupporting
confidence: 93%
“…27,28 These findings were similar to the previous results. The decrease of PTH after nonabdominal surgery in this study was probably attributed to the high proportion of parathyroidectomy, which was the side-effect of parathyroidectomy, 29 but not to APD. In addition, APD treatment has a side effect, that is, the patient's albumin decreased significantly, considered may be related to the surgical stress consumption and APD itself lead to protein loss.…”
Section: Discussionmentioning
confidence: 50%